Neets Phenomenon of Young Romanians Caught Between Never Endless Educational Reform and the Impenetrable Labor Market - Niță, Andreea Mihaela (European Scientific Journal, ESJ, 2017)
In a society genetically endowed with great cognitive potential, the paradigmatic failure of the post-communist education system divide young people into three categories: young elitists who join foreign universities and companies, well-prepared young people eager to study in their country and young NEETs. The increasing percentage of the latter ones is confirmed by the national results obtained in the PISA tests and high school dropout rates. No community in this world can be strong when the investment in education lacks. Non-aligned job policies to educational ones will give birth to worrying imbalances, highlighting the phenomenon of migration. Demographic decline and the lack of strategies to stimulate birth rate will increase the impossibility to ensure generational change within the active population and all these will lead to a block of the pension system. Romania, in the next 20 years will follow the model of the European countries, which face labor importation and the migration of non-European capital. Are there any solutions to counterbalance these trends? This is the question which, the whole rethink of theoretical-methodological analysis of some policies meant to give value to the huge Romanian qualitative human force, deprecated within the large globalization, is based on.